A dose-response meta-analysis of the association between the maternal omega-3 long-chain polyunsaturated fatty acids supplement and risk of asthma/wheeze in offspring - Yin Jia; Yafang Huang; Huili Wang; Haili Jiang (BMC Pediatrics, 2022)
Abstract Background Prenatal exposure to omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) in oily fish may prevent asthma or wheeze in childhood. Objective By limiting n-3 LC-PUFA capsules interventions commenced in pregnancy, this systematic review aimed to find more clear evidence on the relationship between the supplement with n-3 LC-PUFA during pregnancy and the risk of asthma/wheeze in offspring and to improve the life satisfaction of children with asthma. Methods The Cochrane library, Embase, Medline, Web of Science, and PubMed were searched from origin to March 2021 in the above-mentioned databases. Studies selection, data of characteristics extraction, and risk of bias assessment were conducted by two authors, independently. A total of 3037 mother-infant pairs from eight randomized controlled trials were ultimately analyzed. The primary outcome was the risk of “asthma and/or wheeze”, and the secondary outcome was “Allergic asthma” in this dose-response meta-analysis. Sensitivity analysis and subgroup analysis were conducted. The robust-error meta-regression model was used for dose-response analysis. Results This meta-analysis showed that n-3 LC-PUFA during pregnancy did not obviously reduce the risk of asthma/wheeze (RR 0.93; 95% CI 0.82 to 1.04, p = 0.21) and allergic asthma (RR 0.66, 95% CI 0.24 to 1.86, p = 0.44). The risk of asthma/wheeze in offspring was significantly decreased in the subgroup analysis when:: (1) studies conducted in Europe (RR 0.69; 95% CI 0.53 to 0.89); (2) daily supplementary dose of n-3 LC-PUFA was at least 1200 mg (RR 0.69; 95% CI 0.55 to 0.88); (3) supplementation lasts from pregnancy to lactation period (RR 0.69; 95% CI 0.51 to 0.95). Furthermore, the risk of asthma/wheeze reduce 2% when daily supplemental dose of n-3 LC-PUFA was increased by 100 mg in the linear dose-response analysis model. Conclusions Perinatal supplementation with n-3 LC-PUFA can reduce the incidence of asthma/wheeze and allergic asthma in children under certain conditions, and higher doses indicate better protective effects. Further studies are required to confirm the hypothesis of an association between n-3 LC-PUFA intake and childhood asthma/wheeze prevention.